LncRNA CAR10 Upregulates PDPK1 to Promote Cervical Cancer Development by Sponging miR-125b-5p - Hu, Tingting (Biomed Res Int, 2020)
Cervical cancer is one of the malignant tumors that seriously threaten women's health. The mechanism of development needs to be deeply studied. In recent years, lncRNA has been identified as one of the important factors affecting the malignant progression of tumors. In this study, we illustrated the important mechanism of lncRNA CAR10 in the development of cervical cancer. We found that CAR10 is significantly increased in4 cervical cancer tissues and cells, which can promote the proliferation of cervical cancer cells in vitro and in vivo, indicating that CAR10 is involved in the progression of cervical cancer as an oncogene. Further studies showed that CAR10 is a target gene of miR-125b-5p, and miR-125b-5p can inhibit the effect of CAR10 on the proliferation of cervical cancer cells. In addition, we also found that 3-phosphoinositide-dependent protein kinase 1 (PDPK1) is also a target gene of miR-125b-5p, and CAR10 can upregulate the expression level of PDPK1. The results showed that CAR10 acts as a ceRNA to upregulate the expression of PDPK1 by sponging miR-125b-5p. Knockdown of PDPK1 can inhibit the effect of CAR10 on cervical cancer cells. Our study demonstrates that, based on ceRNA mechanism, CAR10/miR-125b-5p/PDPK1 network can regulate the proliferation of cervical cancer cells and play an important role in the development of cervical cancer. In addition, our study also suggests that intervention of CAR10/miR-125b-5p/PDPK1 network may be a new strategy for targeted therapy of cervical cancer.